Thermo-economic analysis of a novel partial cascade organic-steam Rankine cycle. (1st May 2023) - Li, Pengcheng; Qian, Tongle; Li, Jing; Lin, Haiwei; Wang, Yandong; Pei, Gang; Jie, Desuan; Liu, Dongming
Highlights: A novel partial cascade organic-steam Rankine cycle is proposed. The evaporation temperature of the power fluid is elevated to 400 °C. The partial cascade cycle increases the power efficiency by more than 7%. Its potential in heat battery and solar power generation application is explored. An equivalent payback period within 4 years is achievable. Abstract: Conventional heat batteries and concentrated solar power systems adopt subcritical steam Rankine cycles (SRCs) to avoid the technical challenges of supercritical cycles. The water evaporation temperature of 310–337 °C and live steam pressure of 10–14 MPa limit the cycle efficiency (around 42%). This paper proposes a novel partial cascade organic-steam Rankine cycle (ORC-SRC) system to increase the fluid evaporation temperature and thermal efficiency. The ORC-SRC uses a mixture of biphenyl and diphenyl oxide as the top cycle fluid. The mixture absorbs heat from the molten salts and evaporates at about 400 °C to drive a turbine, and then the exhaust vapor releases heat to the bottom SRC. The ORC contributes to saturated steam generation, and molten salts supply the rest heat to the SRC through the steam superheater and reheater. The fundamentals of the system are illustrated, and mathematical models are built. Thermo-economic performance of the system is investigated. The results show that the proposed system significantly increases the average temperature of the power fluid in the heating process, leading to a maximum cycle efficiency of 45.3%. Meanwhile, the moderate live steam pressure of 7.44 MPa in the SRC reduces the leakage loss of the high-pressure turbine and equipment costs. Despite a smaller temperature drop of molten salts during discharge, the equivalent payback period of the ORC-SRC is within 4 years.